Effect of Enriched Environment on Gross Motor Control in Cerebral Palsy - Shagufta Manan, Farwa Maheen, Anam Anwar, Amena Batool, Seerat Fatima, Maryam Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective of study: To evaluate the usefulness of Enriched environment (EE) and Neuro Developmental Technique (NDT) in the perspective of gross motor function in cerebral palsy (CP) . Methodology: This Randomized control trial (RCT) was conducted from March 2016 to November 2016 in Armed Forces Institute of Rehabilitation Medicine Rawalpindi, Pakistan. Sample size was 40 CP children. The data was gathered from 1 to 6 years of spastic CP children through a standard Gross motor function measure (GMFM)tool. This statistical analysis was done on SPSS 21. To evaluate the inferential statistics, independent sample and paired t-test was applied. Results: Participants' average ages in groups A and B were respectively 4.01.7 and 3.81.8. According to our findings, both the treatment group and the control group had significant change (p=0.00). This shows that EE therapy had a significant impact on the children with CP who are spastic; p 0.05. Practical implication: This research will help to incorporate appropriate treatment in the rehabilitation settings to gain effective results. Conclusion: EE plays an effective role in improvement of gross motor function of spastic CP children. But NDT treatment approach was also effective, although less than EE. Key words: Cerebral palsy, Enriched Environment, Neuro-developmental treatment, GMFM